Trust-based quality awareness using combinatorial auction web service selection in service-based systems. (4th November 2019) - Pawar, Suvarna S.; Yalla, Prasanth
With the immense growth and development of the computing exemplar in service-based systems (SBS), the establishment of the engineering architectures has taken new standards. The computation of trust parameter has become vital and essential to measure the quality of services in such service-based systems. This becomes critical and challenging to the success of multi-tier cloud services. Various approaches have been put forth using the quality aware selection mechanisms, but reliability is a major issue in such systems. In order to establish a more reliable service-based systems, the concept of trust awareness is proposed in the present research work and trust-based quality aware selection using combinatorial auction for service oriented systems is presented. Simulation analysis show that the trust-based quality aware service selection scheme provide better accuracy, high success rate, less cost and reduced overhead than the normal combinatorial auction service selection schemes.